First records of Isohypsibius pushkini Tumanov, 2003 (Tardigrada, Eutardigrada, Hypsibiidae) from Poland - Kaczmarek, Łukasz; Gołdyn, Bartłomiej; Czyż, Michał; Michalczyk, Łukasz (Biological Letters, 2011)
First records of Isohypsibius pushkini from small ponds in western Poland are described. So far, these are the only records of this species apart from its type locality in Russia. We present some remarks on the ecology of the species, as well. Moreover, we present the first ever microphotographs of I. pushkini.